Real-world analysis of acamprosate use in patients with cirrhosis and alcohol-associated hepatitis - Oldroyd, Christopher; Wood, Jonathan; Allison, Michael (BMJ Open Gastroenterology, 2024)
Objective Preventing return to alcohol is of critical importance for patients with alcohol-related cirrhosis and/or alcohol-associated hepatitis. Acamprosate is a widely used treatment for alcohol use disorder (AUD). We assessed the impact of acamprosate prescription in patients with advanced liver disease on abstinence rates and clinical outcomes. Methods This was a retrospective case–control study. We reviewed data on all patients admitted to a large tertiary centre in the UK with alcohol-related cirrhosis and/or alcohol-associated hepatitis. We used propensity risk score matching to match patients prescribed acamprosate to controls. The primary outcome was repeat hospitalisation. Results There were 451 patients who met the inclusion criteria of whom 55 patients were started on acamprosate during their admission. Before matching there were significant differences between the cohorts. Patients who received acamprosate were younger (median age 51 vs 57, p<0.005), more likely to have a purely alcohol-related admission (53% vs 24%, p<0.001), and more likely to suffer from a comorbid psychiatric diagnosis (42% vs 20%, p<0.001). On average patients who were started on acamprosate consumed more alcohol (median 155 units/week vs 80 units/week, p<0.001), were less likely to have a partner (35% vs 54%, p 0.006) and more likely to be unemployed (67% vs 44%, p<0.001). After matching for factors with significant differences between groups, we generated a cohort of 53 patients prescribed acamprosate and 53 matched controls. At 1 year there was a significantly higher rate of readmission (85% vs 57%, p<0.001) in the acamprosate group. There were no statistically significant differences in abstinence rates or mortality at 1 year. Conclusion Acamprosate prescription was associated with higher rates of readmission in patients with cirrhosis and/or alcohol-associated hepatitis. This may reflect a greater severity of AUD in those patients or might indicate the limited ability of acamprosate to alter the disease course in this population.